Supporting vocabulary development in children who use Augmentative and Alternative Communication - Smith, Martine (My University, 2015)
Background: Vocabulary development is a powerful driver of language development and is also an important predictor of early progress in reading. It is recommended that vocabulary interventions support rich word knowledge, incorporating phonological, semantic, morphological and orthographic information. Children who use AAC are at risk of vocabulary difficulties. For these children, acquiring vocabulary also involves knowledge of symbol representations and operational skills. Furthermore, they also frequently struggle to develop functional skills in reading and spelling. Method: Four children who use AAC participated in a storybook-based intervention study targeting vocabulary instruction over a ten-week period. The program was structured to integrate communication, language and literacy dimensions of word learning, within a framework where multiple opportunities were provided to see, hear, analyze and use the target words. Results: All children demonstrated increased word knowledge post-intervention, although the areas and the extent of progress varied across participants. Two participants made greater gains in communicative use of target words while two made most progress in spelling. Conclusion: Although small in scope, this study suggests that integrated intervention programs that target multiple aspects of word knowledge can support both communicative and literacy aspects of word learning. Implications for future developments are considered.
PUBLISHED
Keywords: Literacy; Integrated intervention; Aided communication; Vocabulary instruction; Inclusive Society; Language Acquisition (first & second); Language acquisition